Antireflection member, and polarizer, image display device and antireflection article including antireflection member

The antireflection member with a controlled Si:C ratio and uniform silica particle distribution addresses the issue of poor scratch resistance in resin-based layers by enhancing durability and reducing particle chipping, achieving low reflectance and improved resistance to scratches and oil dust.

JP2024177312AActive Publication Date: 2024-12-19DAI NIPPON PRINTING CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024172969
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-03-29
Filing Date
2024-10-02
Publication Date
2024-12-19
Estimated Expiration
2040-01-10

AI Technical Summary

Technical Problem

Existing antireflection members with resin layers in touch panel image display devices suffer from poor abrasion resistance and scratch resistance, particularly when used with fingers covered in oil or sand, due to the chipping or falling off of hollow silica particles from the low refractive index layer.

Method used

The antireflection member is designed with a low refractive index layer containing a binder resin and silica particles, where the surface area ratio of Si element to C element is between 10.0 atomic % and 18.0 atomic %, and the ratio of C element is between 180 atomic % and 500 atomic %, with controlled distribution of hollow and non-hollow silica particles, ensuring they are coated with a silane coupling agent and uniformly dispersed, thereby enhancing scratch resistance.

Benefits of technology

The solution provides an antireflection member with low reflectance and excellent surface durability, including high scratch resistance and oil dust resistance, outperforming conventional methods in both fluorescent and LED lighting conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024177312000001_ABST
    Figure 2024177312000001_ABST
Patent Text Reader

Abstract

To provide an antireflection member having low reflectance and improved excoriation resistance, and an image display device including the antireflection member.SOLUTION: An antireflection member 100 includes a low reflective index layer 130 on a transparent base material 110. The low refractive index layer 130 contains a binder resin and silica particles 132 and 134. The ratio of a Si element attributed to the silica particles obtained by analyzing the surface region of the low refractive index layer 130 by X-ray photoelectron spectroscopy is 10.0 atomic% or more and 18.0 atomic% or less, and when the ratio of the Si element is converted to 100 atomic%, the ratio of the C element is 180 atomic% or more and 500 atomic% or less.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an antireflection member, and a polarizing plate, an image display device, and an antireflection article each including the antireflection member. [Background technology]

[0002] It is known that in display devices such as liquid crystal display devices, organic EL display devices, micro LED display devices, showcases, etc., an anti-reflection member is provided on the device surface to improve visibility. In recent years, in addition to televisions, touch panel type image display devices such as in-vehicle displays such as car navigation systems, tablets, smartphones, etc., which are operated by users directly touching the screen, have become widespread, and these devices are also provided with an anti-reflection member.

[0003] Known methods for producing an anti-reflection member include a method of laminating an inorganic thin film having a different refractive index as an anti-reflection layer on a hard coat layer provided on a transparent substrate by dry film formation such as a sputtering method, and a method of forming an anti-reflection layer by coating a resin containing fine particles on a hard coat layer. In general, an anti-reflection member having a resin layer formed thereon has the advantages of having a smaller change in oblique reflection hue, excellent chemical stability (especially alkali resistance), and low cost compared to a case where an inorganic thin film is formed. On the other hand, an anti-reflection member having a resin layer formed thereon tends to have inferior mechanical properties such as scratch resistance and a higher reflectance compared to a case where an inorganic thin film is formed.

[0004] To address this issue, for example, Patent Documents 1 and 2 disclose that hollow inorganic nanoparticles such as silica and solid inorganic nanoparticles are contained in the low refractive index layer. Furthermore, the solid inorganic nanoparticles are unevenly distributed on the interface side with the hard coat, and the hollow inorganic nanoparticles are unevenly distributed on the opposite side of the interface. This achieves both high scratch resistance (abrasion resistance) and low reflectance.

[0005] Patent Document 3 discloses that reactive silica microparticles in a low refractive index layer are unevenly distributed at the interface on the hard coat layer side and / or the interface on the opposite side to the hard coat layer, and hollow silica microparticles are densely packed in the low refractive index layer, thereby improving surface hardness (scratch resistance).

[0006] Patent Document 4 discloses that an anti-reflection film is formed on an optical substrate, in which hollow silica particles and fine silica particles are dispersed in a binder containing reactive silanes as a main component. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Special Publication No. 2018-533068 [Patent Document 2] Special Publication No. 2018-533762 [Patent Document 3] Patent No. 6011527 [Patent Document 4] JP 2007-078711 A DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]

[0008] However, even if silica fine particles are added to the low refractive index layer as in the above patent document, the antireflection member having a resin layer formed thereon has a limited steel wool resistance, and there still remains a problem that the scratch resistance is poorer than that of an inorganic thin film formed by a known dry film formation method such as sputtering. In particular, when an antireflection member having a resin layer formed thereon is applied to a touch panel type image display device, there is a problem that the surface may be scratched simply by operating the device with a user's finger.

[0009] Furthermore, when an anti-reflection film is formed using a binder made of reactive silanes as in Patent Document 4, there has been a problem in that sufficient scratch resistance cannot be obtained.

[0010] In view of the above-mentioned problems, the present invention aims to provide an antireflection member having low reflectance and improved scratch resistance, and an antireflection member, as well as a polarizing plate, an image display device, and an antireflection article each including the antireflection member. [Means for solving the problem]

[0011] The present inventors have found that, even if scratches are not visible when the resin layer surface is rubbed only with fine solid matter (e.g., sand) or only with oil, scratches are caused on the resin layer surface when the resin layer surface is rubbed with something that has oil containing solid matter attached. This corresponds to, for example, a user operating a touch panel type image display device with a finger that has oil contained in cosmetics and food and sand contained in the air attached thereto.

[0012] As a result of the study by the present inventors, it was found that the above-mentioned scratches are mainly caused by a part of the hollow silica particles contained in the low refractive index layer being chipped or the hollow silica particles falling off. It was considered that the cause of this is that the unevenness caused by the hollow silica particles formed on the surface of the low refractive index layer is large. That is, when the surface of the low refractive index layer is rubbed with a finger with oil containing solid matter such as sand, the oil becomes a binder and the finger moves on the surface of the low refractive index layer with the solid matter still attached to the finger. At this time, the phenomenon that a part of the solid matter (for example, a sharp part of sand) enters the recess of the low refractive index layer surface, and the phenomenon that the solid matter that entered the recess passes through the recess together with the finger and overcomes the protrusion (hollow silica particle) is likely to occur, and at that time, a large force is applied to the protrusion (hollow silica particle), so it was considered that the hollow silica particles are damaged or fall off. It was also considered that the resin itself located in the recess is scratched by friction with the solid matter, and the hollow silica particles are more likely to fall off due to the damage. Therefore, the inventors have intensively studied methods for solving the above problems and have succeeded in obtaining an antireflection member having a smooth low refractive index layer surface, low reflectance, and excellent surface durability such as high scratch resistance, thereby completing the present invention.

[0013] In order to solve the above problems, the present invention provides the following [1] to

[12] . [1] An antireflection member comprising a low refractive index layer on a transparent substrate, the low refractive index layer containing a binder resin and silica particles, and an analysis of a surface region of the low refractive index layer by X-ray photoelectron spectroscopy reveals that the ratio of Si element attributable to the silica particles is 10.0 atomic % or more and 18.0 atomic % or less, and the ratio of C element, when the ratio of Si element is converted to 100 atomic %, is 180 atomic % or more and 500 atomic % or less. [2] The antireflection member according to [1], wherein the silica particles are hollow silica particles and non-hollow silica particles. [3] The antireflection member according to [2], wherein the ratio of the average particle size of the non-hollow silica particles to the average particle size of the hollow silica particles is 0.29 or less. [4] The antireflection member according to [2] or [3], wherein the hollow silica particles have an average particle size of 50 nm or more and 100 nm or less, and the non-hollow silica particles have an average particle size of 5 nm or more and 20 nm or less. [5] The antireflection member according to any one of [2] to [4], wherein the surfaces of the hollow silica particles and the non-hollow silica particles are coated with a silane coupling agent. [6] The antireflection member according to [1], wherein the surface region of the low refractive index layer is substantially free of fluorine atoms. [7] The antireflection member according to any one of [1] to [6], wherein the low refractive index layer has an indentation hardness of 480 MPa or more by a nanoindentation method. [8] The antireflection member according to any one of [1] to [7], wherein the low refractive index layer has a restoration rate of 80% or more by a nanoindentation method. [9] The antireflection member according to any one of [1] to [8], wherein Rz / Ra is 22.0 or less, where Rz is the maximum height roughness of the surface of the low refractive index layer and Ra is the arithmetic mean roughness of the surface of the low refractive index layer.

[10] A polarizing plate having a transparent protective plate, a polarizer, and a transparent protective plate in this order, at least one of the two transparent protective plates being the anti-reflection member described in any one of [1] to [9].

[11] An image display device comprising an antireflection member according to any one of [1] to [9] above a display element.

[12] An antireflective article comprising the antireflective member according to any one of [1] to [9] on a member. Effect of the Invention

[0014] According to the present invention, an antireflection member having a low reflectance and excellent surface resistance such as scratch resistance can be obtained. [Brief description of the drawings]

[0015] [Figure 1] 1 is a schematic cross-sectional view illustrating an embodiment of an antireflection member of the present invention. [Diagram 2] FIG. 4 is a schematic cross-sectional view illustrating another embodiment of an antireflection member of the present invention. [Diagram 3] 3 is a cross-sectional image of a low refractive index layer in Example 1. [Figure 4] 1 is a cross-sectional image of a low refractive index layer in Comparative Example 2. [Diagram 5] 11 is a cross-sectional image of a low refractive index layer in Comparative Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The antireflection member of the present invention will be described in detail below. In this specification, the expression "AA to BB" as a numerical range means "not less than AA and not more than BB".

[0017] [Anti-reflective material] The antireflection member of the present invention is an antireflection member comprising a low refractive index layer on a transparent substrate, the low refractive index layer containing a binder resin and silica particles, and the ratio of Si element attributable to the silica particles, obtained by analyzing a surface region of the low refractive index layer by X-ray photoelectron spectroscopy, is 10.0 atomic % or more and 18.0 atomic % or less, and the ratio of C element, when the ratio of Si element is converted to 100 atomic %, is 180 atomic % or more and 500 atomic % or less. The silica particles preferably include hollow silica particles and non-hollow silica particles.

[0018] Fig. 1 is a cross-sectional schematic diagram illustrating an embodiment of an antireflection member of the present invention. The antireflection member 100 in Fig. 1 is configured by laminating a hard coat layer 120 and a low refractive index layer 130 in this order on one surface of a transparent substrate 110. The low refractive index layer 130 contains hollow silica particles 132 and non-hollow silica particles 134 as silica particles.

[0019] Fig. 2 is a schematic cross-sectional view illustrating another embodiment of the antireflection member of the present invention. The antireflection member 200 in Fig. 2 has a high refractive index layer 140 between a hard coat layer 120 and a low refractive index layer 130. The high refractive index layer 140 contains inorganic fine particles 142 having a high refractive index.

[0020] [Properties of anti-reflective materials] <Optical properties> The antireflection member of the present invention preferably has a luminous reflectance Y value of 1.0% or less, more preferably 0.5% or less, measured at a light incidence angle of 5 degrees from the side having the low refractive index layer. In this specification, the luminous reflectance Y value refers to the luminous reflectance Y value of the CIE1931 standard color system. The luminous reflectance Y value can be calculated using a spectrophotometer (for example, Shimadzu Corporation, product name "UV-3600plus"). In general, the luminous reflectance Y value of an antireflection member formed by a sputtering method having four or five layers (hereinafter referred to as a "dry antireflection member") is 0.5% or less. The antireflection member of the present invention exhibits a low reflectance comparable to that of a dry antireflection member. Furthermore, the antireflection member of the present invention exhibits a smaller change in luminous reflectance when the light incidence angle is increased than that of a dry antireflection member, i.e., the change in oblique reflection hue is smaller.

[0021] The antireflection member of the present invention preferably has a total light transmittance of 50% or more, more preferably 80% or more, and even more preferably 90% or more according to JIS K7361-1: 1997. The total light transmittance and the haze described below can be measured, for example, with a haze meter (product number: HM-150) manufactured by Murakami Color Research Laboratory.

[0022] The antireflection member of the present invention preferably has a haze of 1.0% or less, more preferably 0.5% or less, and even more preferably 0.2% or less, as determined by JIS K7136:2000. However, this does not apply when antiglare properties are imparted. When emphasis is placed on transmission clarity and contrast, the haze is preferably less than 5.0%, and when emphasis is placed on antiglare properties, the haze is preferably 5 to 50%.

[0023] <Elemental analysis of the surface region of the low refractive index layer> When the surface of the low refractive index layer of the antireflection member of the present invention is analyzed by X-ray photoelectron spectroscopy (hereinafter simply referred to as "XPS"), at least the C element, the O element, and the Si element are detected. The Si element originates from silica particles (inorganic component) and organic components such as a silane coupling agent and a leveling agent. The C element originates from the binder resin, the surface treatment agent for the silica particles (silane coupling agent), and additives. However, considering the content in the low refractive index layer, the C element can be considered to be substantially derived from the binder resin.

[0024] The surface region of the low refractive index layer of the present invention analyzed by XPS shows that the ratio of Si element belonging to silica particles is 10.0 atomic % or more and 18.0 atomic % or less, and the ratio of C element when the ratio of the Si element is converted to 100 atomic % is 180 atomic % or more and 500 atomic % or less. In the present invention, the "surface region" is within the range of the detection region by X-ray photoelectron spectroscopy, and refers to the region from the surface of the low refractive index layer opposite to the hard coat layer to a depth of 10 nm. The "ratio of C element when the ratio of Si element is converted to 100 atomic %" can be calculated by "C / Si x 100 (%)". Hereinafter, the "ratio of C element when the ratio of Si element is converted to 100 atomic %" may be abbreviated as "C / Si". In addition, since the Si considered in the present invention is inorganic Si element belonging to silica particles, Si means inorganic Si element unless otherwise specified.

[0025] The C / Si in the surface region of the low refractive index layer reflects the distribution state of the solid silica particles and hollow silica particles in the thickness direction of the low refractive index layer. When silica particles are unevenly distributed on the opposite side (hard coat layer side) of the low refractive index layer, the ratio of Si element belonging to the silica particles in the surface region is low, and the ratio of C element is relatively high. The same tendency occurs when silica particles are buried in the binder resin and are hardly present on the surface of the low refractive index layer. When silica particles (especially hollow silica particles) are exposed to the surface of the low refractive index layer without being covered by the binder resin, the ratio of Si element belonging to the silica particles is high, and the ratio of C element is relatively low.

[0026] The ratio of Si element belonging to silica particles in the surface region of the low refractive index layer reflects the presence state of non-hollow silica particles and hollow silica particles in the surface region. Even if hollow silica is present in a large amount in the surface region of the low refractive index layer, it does not contribute much to the increase in the ratio of Si element belonging to silica particles because it is hollow, but when non-hollow silica is present in a large amount in the surface region, the ratio of Si element belonging to silica particles becomes high. When silica particles are present in a sufficient amount in the surface region of the low refractive index layer, the ratio of Si element belonging to silica particles in the surface region of the low refractive index layer satisfies 10.0 atomic % or more. In particular, when the ratio of Si element belonging to silica particles is 13.0 atomic % or more, non-hollow silica particles are present in high concentration on the surface side, which is preferable because it improves scratch resistance. On the other hand, when the ratio of Si element belonging to silica particles exceeds 18.0 atomic %, not only non-hollow silica but also hollow silica particles are present in a large amount in the surface region and are exposed to the surface, which causes a decrease in scratch resistance as described below. In addition, the silica particles are present in a sufficient amount in the surface region of the low refractive index layer, so that C / Si satisfies 500 atomic % or less. If C / Si exceeds 500 atomic %, the silica particles are buried in the binder resin, and the binder resin becomes excessive in the surface region, resulting in insufficient scratch resistance. On the other hand, if C / Si is less than 180 atomic %, the amount of silica particles present on the surface increases, and in particular, hollow silica particles not covered with the binder resin are exposed to the surface, causing a decrease in scratch resistance. Considering scratch resistance and sufficient coverage, C / Si is preferably 200 atomic % or more, more preferably 250 atomic % or more. In addition, C / Si is preferably 400 atomic % or less, more preferably 350 atomic % or less.

[0027] By setting the ratio of C element and the ratio of Si element in the surface region of the low refractive index layer within the above range, the hollow silica particles can be covered with an appropriate amount of binder resin, and a sufficient amount of non-hollow silica particles can be present in the gaps between the hollow silica particles. This makes it possible to obtain an antireflection member that has a low reflectance and excellent surface durability such as high scratch resistance while making the surface of the low refractive index layer smoother.

[0028] Also, as in Patent Document 4, when a low refractive index layer is formed using reactive silanes as a binder raw material, C / Si becomes a very small value. That is, the C / Si is different between a low refractive index layer using reactive silanes as a binder raw material and a low refractive index layer using a resin as a binder. In the case of a low refractive index layer using reactive silanes as a binder raw material, scratch resistance and the like deteriorate due to the influence of the binder component. Therefore, it can be said that an antireflection member having excellent surface resistance such as high scratch resistance can be obtained by setting C / Si in the surface region of the low refractive index layer to 180 atomic % or more and 500 atomic % or less.

[0029] Even if the coating liquid for forming a low refractive index layer does not contain a fluorine-containing compound such as a fluorine-based leveling agent, fluorine may be detected on the surface of the formed low refractive index layer. This is because a fluorine-based leveling agent is contained in the hard coat layer serving as the base layer of the low refractive index layer and in the lower layers such as the high refractive index layer described below, and the fluorine-based leveling agent diffuses through the low refractive index layer during the formation of the low refractive index layer and migrates to the surface of the low refractive index layer. In the antireflection member of the present invention, even if the lower layer contains a fluorine-based leveling agent (fluorine-containing compound), it may be preferable that F element is not detected by XPS. That is, it may be preferable that the surface region of the low refractive index layer does not substantially contain fluorine atoms. If a fluorine-containing compound is present in the surface region, the binder resin itself may be easily scratched, and the hollow silica particles may be easily dropped off, depending on the processing conditions. That is, in such a case, if the low refractive index layer contains a fluorine-containing compound, it causes a decrease in scratch resistance. This is presumably because the fluorine-containing compound itself is soft, and the hardness of the binder resin itself is reduced. By the low refractive index layer showing the above element ratio and containing silica particles at a high concentration relative to the binder resin, the diffusion of the fluorine-containing compound can be suppressed, and the surface region can be easily made to be substantially free of F atoms. In addition, in this specification, "substantially free of fluorine atoms" means that the ratio of F element in the surface region is 0.5 atomic % or less, more preferably 0.1 atomic % or less.

[0030] Since the surface region of the low refractive index layer of the antireflection member of the present invention has the above element ratio, it also has the effect of having high gas barrier properties (water vapor permeability and oxygen gas permeability).

[0031] <Dispersion state of silica particles> In order to achieve the above-mentioned element ratio, it is preferable that the hollow silica particles and non-hollow silica particles are uniformly dispersed in the low refractive index layer of the antireflection member of the present invention. In the present invention, "uniformly dispersed" means that the hollow silica particles and non-hollow silica particles are not only uniformly dispersed in the surface region of the low refractive index layer, but also uniformly dispersed in the thickness direction of the low refractive index layer when viewed in cross section. That is, when XPS analysis is performed in the thickness direction of the low refractive index layer, it is preferable that the ratio of Si element belonging to the silica particles and C / Si satisfy the above-mentioned range at different positions in the thickness direction. For example, when the thickness of the low refractive index layer is divided into three equal parts and defined as a first region, a second region, and a third region in order from the transparent substrate side, it is preferable that the ratio of Si element belonging to the silica particles and C / Si satisfy the above-mentioned range at any position in the first region and any position in the second region.

[0032] FIG. 3 is a cross-sectional image of the low refractive index layer in the antireflection member of Example 1 of the present invention, observed by a transmission electron microscope (TEM). In the low refractive index layer of the present invention, non-hollow silica particles (solid silica particles) are present in large quantities not only at the interface between the low refractive index layer and the hard coat layer, but also on the surface of the low refractive index layer (the surface opposite to the hard coat layer) together with the binder resin. A plurality of hollow silica particles are arranged in the thickness direction. From the image of FIG. 3, it is considered that the non-hollow silica particles are uniformly dispersed in the thickness direction of the low refractive index layer. In addition, it can be confirmed that the hollow silica particles have a small protrusion amount from the surface of the low refractive index layer and are covered with the binder resin.

[0033] 4 and 5 show cross-sectional images of an example of a low refractive index layer having poor particle dispersibility. Fig. 4 is a cross-sectional image of the low refractive index layer in the antireflection member of Comparative Example 2, observed by a transmission electron microscope. In Fig. 4, it can be seen that non-hollow silica particles (solid silica particles) are distributed densely at the interface between the low refractive index layer and the hard coat layer. It can also be seen that the hollow silica particles protrude significantly from the surface of the low refractive index layer and are exposed without being covered by the binder resin. Fig. 5 is a cross-sectional image obtained by observing with a scanning electron microscope (SEM) the low refractive index layer in the antireflection member of Comparative Example 5. In Fig. 5, it can be seen that non-hollow silica particles (solid silica particles) are densely and unevenly distributed on the surface of the low refractive index layer.

[0034] The cross-sectional images of Figures 3 and 4 were obtained by observation using an electron microscope H-7650 manufactured by Hitachi High-Technologies Corporation under conditions of an emission current of 10 μA, an acceleration voltage of 100 keV, and a filament voltage of 20 V. The cross-sectional image of Figure 5 was obtained by observation using an electron microscope S-4800 manufactured by Hitachi High-Technologies Corporation under conditions of an emission current of 10 μA, and an acceleration voltage of 30 keV.

[0035] <Scratch resistance> The low refractive index layer of the antireflection member of the present invention is excellent in terms of scratch resistance, that is, resistance to steel wool and resistance to oil dust. Generally, pencil hardness is known as an index of the scratch resistance of the surface of an optical member such as an anti-reflection member. However, pencil hardness is used to evaluate the resistance when a hard material comes into contact with the surface under a stress similar to a point load. On the other hand, repeated friction or long-term use often results in minute scratches caused by gentle surface loads. It is appropriate to evaluate the resistance to such scratches using steel wool resistance and oil dust resistance, which are indices different from pencil hardness.

[0036] In the present invention, the steel wool resistance is defined as the maximum load at which no scratches on the low refractive index layer are observed with the naked eye (zero scratches) when the surface of the low refractive index layer is rubbed with steel wool while applying a load under the following conditions, and then the angle between the light emitting part and the object is changed and observation is performed. The observation is performed under a fluorescent lamp (illuminance: 200 to 2000 Lx, for example, a three-wavelength fluorescent lamp manufactured by Panasonic Corporation, model number: FHF32EX-NH) and an LED lamp (illuminance: 100 to 8000 Lx, for example, manufactured by Ohm Electric Co., Ltd., model number: LPL-48N), respectively, and the distance from the light emitting part to the object is 10 cm to 300 cm. The area of ​​the steel wool in contact with the target (the surface of the low refractive index layer) is 0.5 to 1.5 cm2 The shape of the surface where the steel wool comes into contact with the object can be circular, triangular, polygonal, etc., but circular is preferable. In the test, the steel wool is moved at the same location a one-way distance of 30 mm or more (a one-way travel distance of 60 mm or more). The one-way travel distance is set appropriately depending on the size of the device to which the anti-reflection material is applied. <Test conditions> Steel wool: Made by Japan Steel Wool Co., Ltd., Product name: Bonstar, Product code: #0000 Traveling speed: 100mm / sec Number of round trips: 10

[0037] The antireflection member of the present invention has a steel wool resistance of the low refractive index layer of 750 g / cm under fluorescent lamp. 2 It is preferable that the thickness is 900 g / cm or more. 2 More preferably, it is 1000 g / cm or more. 2 More preferably, it is 1200 g / cm or more. 2 It is particularly preferable that the low refractive index layer has a steel wool resistance of 450 g / cm under an LED. 2 It is preferable that the density is 500 g / cm or more. 2 More preferably, it is 600 g / cm or more. 2 More preferably, it is 700 g / cm or more. 2 More preferably, it is equal to or greater than this. The steel wool resistance of anti-reflection materials made by the conventional wet method is 700 g / cm under fluorescent lighting. 2 Below 200g / cm under LED 2 (minimum inspection load). In the case of a commercially available dry anti-reflection material (a fluorine-based coating film laminated on a five-layer sputtered film of SiO2 as the outermost layer), the steel wool resistance is 1500g / cm under fluorescent lighting. 2 However, under LED, it is 200g / cm 2(minimum inspection load) or less. That is, the antireflection member of the present invention has higher steel wool resistance than antireflection members produced by conventional wet methods, and can achieve excellent steel wool resistance equivalent to that of dry antireflection members when evaluated under fluorescent lamps. Furthermore, the antireflection member of the present invention has superior steel wool resistance than dry antireflection members when evaluated under LEDs.

[0038] The low refractive index layer in the antireflection member of the present invention has a small amount of hollow silica particles exposed to the surface, and is covered with binder resin.In addition, since non-hollow silica particles are present in a high concentration in the binder resin in the surface region, the hardness of the binder resin itself is increased, and since non-hollow silica particles are uniformly dispersed in the binder resin, it is considered that the shrinkage unevenness during resin curing is suppressed and the surface is smoother.In addition, it can be assumed that, for this reason, when the low refractive index layer of the present invention is rubbed with steel wool, damage or falling off of hollow silica particles and damage to the binder resin itself can be suppressed.

[0039] The oil dust resistance test is a test for judging the scratch marks when a mixture of AC dust and olive oil as specified in ISO12103-1 is soaked into a cloth or rag and rubbed against the surface of an object. Fine (A2), Coarse (A4), or a mixture of Fine (A2) and Coarse (A4) can be used as the AC dust. In the present invention, the oil dust resistance is the maximum load when scratches on the low refractive index layer are not observed with the naked eye (zero scratches) after rubbing the surface of the low refractive index layer with a cloth or rag soaked in the mixture while applying a load under the following conditions. Observation is performed under fluorescent lamps (illuminance: 200 to 2000 Lx) and LEDs (illuminance: 100 to 8000 Lx), respectively, and the distance from the light emitting part to the object is 10 cm to 300 cm. The oil dust resistance test is carried out by attaching a cloth or rag to the end of the metal member, soaking it in the mixed liquid, and moving the cloth or rag in contact with the object. The shape of the contact surface between the end of the metal member and the object (the surface of the low refractive index layer) can be a triangle, polygon, circle, etc., but a square is preferable. The area of ​​the contact surface is 0.5 to 1.5 cm2. 2 In the test, the cloth or rag is moved a distance of 30 mm or more at the same location, and a round trip of 60 mm or more is performed. The one-way movement distance is set appropriately depending on the size of the device to which the anti-reflection member is applied. <Test conditions> Traveling speed: 100mm / sec Number of round trips: 10

[0040] The low refractive index layer of the antireflection member of the present invention has an oil dust resistance of 700 g / cm under fluorescent lighting. 2 It is preferable that the thickness is 750 g / cm or more. 2 More preferably, it is 800 g / cm or more. 2 More preferably, it is 1200 g / cm or more. 2 The low refractive index layer of the antireflection member of the present invention has an oil dust resistance of 400 g / cm under LED lighting. 2 It is preferable that the thickness is 450 g / cm or more. 2 More preferably, it is 500 g / cm or more. 2 More preferably, it is 900 g / cm or more. 2 More preferably, it is equal to or greater than this. Anti-reflection materials made by conventional wet methods have an oil dust resistance of 200 g / cm under fluorescent lighting. 2 100g / cm under LED 2 (minimum inspection load). In the case of a commercially available dry anti-reflection material (a fluorine-based coating film laminated on a five-layer sputtered film of SiO2 as the outermost layer), the oil dust resistance when evaluated under fluorescent lamps is 1500g / cm 2 On the other hand, when evaluated under LED, the oil dust resistance was 100g / cm 2(minimum inspection load) or less. That is, the antireflection member of the present invention has better oil dust performance than an antireflection member produced by a conventional wet method, both when evaluated under fluorescent lamps and LEDs. Furthermore, the antireflection member of the present invention has excellent oil dust resistance equivalent to that of a conventional dry antireflection member under fluorescent lamps, and further has better oil dust resistance than a conventional dry antireflection member when evaluated under LEDs.

[0041] <Surface roughness> In order to obtain excellent surface resistance, the low refractive index layer in the present invention preferably has a smooth surface. The maximum height roughness Rz may be 110 nm or less, preferably 100 nm or less, and more preferably 90 nm or less. Furthermore, since a smoother surface can obtain even better surface resistance, it is preferably 70 nm or less, and more preferably 60 nm or less. Furthermore, Rz / Ra (Ra is arithmetic mean roughness) is preferably 22.0 or less, more preferably 18.0 or less, even more preferably 16.0 or less, and even more preferably 12.0 or less. In the present invention, Ra and Rz are two-dimensional roughness parameters described in the Scanning Probe Microscope SPM-9600 Upgrade Kit Instruction Manual (SPM-9600 February 2016, pp. 194-195) that are expanded to three dimensions. Ra and Rz are defined as follows. (Arithmetic mean roughness Ra) When only a reference length (L) is cut out from the roughness curve in the direction of the average line, the X-axis is taken in the direction of the average line of this cut-out portion and the Y-axis is taken in the direction of the longitudinal magnification, and the roughness curve is expressed as y = f(x), the following formula can be used.

number

[0042] A small Rz means that the convex portion caused by the hollow silica particles in the micro-region is small. A small Rz / Ra means that the irregularities caused by the silica particles in the micro-region are uniform and do not have protruding irregularities with respect to the average elevation difference of the irregularities. In the present invention, the value of Ra is not particularly limited, but it is sufficient that Ra is 15 nm or less, and more preferably 12 nm or less. In order to obtain even better surface resistance, it is preferably 10 nm or less, and more preferably 6.5 nm or less. By the low refractive index layer showing the above element ratio, a sufficient amount of non-hollow silica particles are present in the binder between hollow silica particles, and hollow silica particles can be present in the surface region in a state of being covered with binder resin without protruding to the surface, and the shrinkage unevenness of the low refractive index layer can be suppressed. Therefore, it is easy to satisfy the above range of Rz and Rz / Ra. The Rz of the surface of the low refractive index layer may become as large as about 90 to 110 nm depending on the processing conditions of the low refractive index layer. In that case, when Rz / Ra is within the above range, it is easy to obtain a preferable surface resistance.

[0043] By setting the Rz and Rz / Ra of the low refractive index layer surface within the above ranges, the resistance when a solid material overcomes the convex parts (caused by hollow silica particles present near the surface) of the low refractive index layer surface can be reduced. Therefore, it is considered that the solid material moves smoothly over the low refractive index layer surface even when rubbed with oily AC dust under a load. It is also considered that the hardness of the concave parts itself is increased. As a result, it can be presumed that the breakage and falling off of the hollow silica particles is prevented, and damage to the binder resin itself is also prevented.

[0044] On the other hand, if the Rz and Rz / Ra of the low refractive index layer surface are too small, blocking may occur during the manufacturing process. Therefore, Rz is preferably 30 nm or more, more preferably 70 nm or more. Also, Rz / Ra is preferably 3.0 or more, more preferably 5.0 or more.

[0045] <Indentation hardness, recovery rate> The low refractive index layer in the present invention preferably has an indentation hardness of 480 MPa or more as measured by a nanoindentation method. The low refractive index layer in the present invention preferably has a recovery rate of 80% or more as measured by a nanoindentation method. By satisfying the above ranges for the indentation hardness and recovery rate, a low refractive index layer having excellent steel wool resistance and oil dust resistance can be obtained.

[0046] The indentation hardness and the recovery rate are affected by the layer below the low refractive index layer (transparent substrate side). In the present invention, the indentation hardness and the recovery rate can be improved by providing a hard coat layer below the low refractive index layer and further providing a high refractive index layer between the low refractive index layer and the hard coat layer.

[0047] Considering the steel wool resistance and oil dust resistance, the indentation hardness is preferably 500 MPa or more, more preferably 550 MPa or more, even more preferably 600 MPa or more, and even more preferably 650 MPa or more. The indentation hardness is preferably 1000 MPa or less, more preferably 950 MPa or less, even more preferably 900 MPa or less, and particularly preferably 800 MPa or less.

[0048] In consideration of the steel wool resistance and oil dust resistance, the recovery rate is preferably 82% or more, more preferably 83% or more, and even more preferably 85% or more.

[0049] Furthermore, the product of the indentation hardness and the recovery rate ([indentation hardness] × [recovery rate] ÷ 100) is an index representing the scratch resistance of the low refractive index layer. In other words, the larger the product of the indentation hardness and the recovery rate, the more excellent the scratch resistance of the low refractive index layer. In the present invention, the product is preferably 380 MPa or more, more preferably 410 MPa or more, and even more preferably 460 MPa or more. Furthermore, the product is preferably 1000 MPa or less, more preferably 950 MPa or less, and even more preferably 900 MPa or less.

[0050] In the present invention, the "indentation hardness" is a value measured and analyzed by a surface film physical property tester (Triboindenter TI950, manufactured by HYSITRON) by the nanoindentation method. A Berkovich indenter (material: triangular diamond pyramid) is pressed into the surface of the low refractive index layer under the following conditions to perform the measurement. In the measurement, the unevenness of the low refractive index surface is observed under a microscope, and a place that is as flat as possible without any particular defects is selected as the measurement point.

[0051] <Indentation hardness measurement conditions> Indenter used: Berkovich indenter (model number: TI-0039, manufactured by HYSITRON) -Indentation condition: Displacement control method Maximum indentation depth: 30 nm Load application time: 3 seconds (speed: 10 nm / sec) Hold Time: 5 seconds Loading / unloading time: 3 seconds (speed: 10 nm / sec)

[0052] The "restoration rate" in the present invention is a value determined by analyzing a load-displacement curve measured by a nanoindentation method using a surface film physical property tester (Triboindenter TI950, manufactured by HYSITRON Corporation). The load-displacement curve is measured by pressing a Berkovich indenter (material: triangular diamond pyramid) into the surface of the low refractive index layer under the following conditions: When measuring, the unevenness of the low refractive index surface is observed under a microscope, and a place that is as flat as possible without any particular defects is selected as the measurement point. <Load-displacement curve measurement conditions> Indenter used: Berkovich indenter (model number: TI-0039, manufactured by HYSITRON) Pressing conditions: Load control method ·Maximum load: 30μN Load application time: 3 seconds (speed: 10μN / sec) Hold Time: 5 seconds Load unloading time: 3 seconds (speed: 10μN / sec)

[0053] From the load-displacement curve data obtained, the total deformation work W total , and elastic deformation work W elast Calculate the total deformation work W total is expressed by the following equation. W total =W elast +W plast W plast : Plastic deformation work W total and W elast The recovery rate (elastic recovery rate) is calculated from the following formula. Recovery rate [%] = (W elast / W total ) x 100

[0054] In this specification, the optical properties, element ratios, surface roughness, indentation hardness, and recovery rate refer to the average values ​​of the measured values ​​at 14 points excluding the minimum and maximum values ​​of the measured values ​​at 16 points, unless otherwise specified. In this specification, the 16 measurement points are preferably centered on 16 intersections of lines drawn from the 0.5 cm margin from the outer edge of the measurement sample to divide the inner area of ​​the margin into 5 equal parts vertically and horizontally. For example, when the measurement sample is a rectangle, it is preferable to measure 16 intersections of lines drawn from the 0.5 cm margin from the outer edge of the rectangle to divide the inner area of ​​the margin into 5 equal parts vertically and horizontally, and calculate the parameters from the average value. In addition, when the measurement sample is a shape other than a rectangle, such as a circle, an ellipse, a triangle, or a pentagon, it is preferable to draw a rectangle inscribed in the shape and measure 16 points on the rectangle by the above method.

[0055] In this specification, the optical properties, surface roughness, indentation hardness, and recovery rate are values ​​measured at a temperature of 23±5°C and a relative humidity of 40 to 65%, unless otherwise specified. In addition, before the start of each measurement and evaluation, the target sample is exposed to the above atmosphere for 30 minutes or more before the measurement and evaluation. For elemental analysis, the target sample is also exposed to the above atmosphere for 30 minutes or more before the measurement.

[0056] The conditions for obtaining the antireflection member of the present invention will be described below. [Transparent base material] The transparent substrate serves as a support for the hard coat layer and the low refractive index layer. The transparent substrate is preferably one having high light transmittance. Specifically, it is preferable that the total light transmittance according to JIS K7361-1:1997 is 90% or more.

[0057] Examples of the transparent substrate include plastic and glass. It is more preferable that the transparent substrate is made of plastic because it is lightweight and easy to manufacture.

[0058] The plastic substrate may be formed from one or more of the following: polyolefin resins such as polyethylene and polypropylene; vinyl resins such as polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, ethylene-vinyl acetate copolymer and ethylene-vinyl alcohol copolymer; polyester resins such as polyethylene terephthalate, polyethylene naphthalate and polybutylene terephthalate; acrylic resins such as polymethyl (meth)acrylate and polyethyl (meth)acrylate; styrene resins such as polystyrene; polyamide resins such as nylon 6 or nylon 66; cellulose resins such as triacetyl cellulose; resins such as polycarbonate; polyimide resins; and cycloolefin resins obtained from cycloolefins such as norbornene and dicyclopentadiene.

[0059] The thickness of the plastic substrate is not particularly limited. From the viewpoint of handling, the thickness of the plastic substrate is preferably 10 to 500 μm, more preferably 20 to 400 μm, and further preferably 50 to 300 μm. The plastic substrate may be a plate-like substrate having a thickness of more than 500 μm. When flexibility is required, such as for foldable applications, the thickness of the plastic substrate is preferably 10 to 40 μm in order to make the antireflection member thin. In addition, when glass is used in the component to which the antireflection member is attached, the thickness of the plastic substrate is preferably 40 to 100 μm in order to prevent the glass from scattering.

[0060] [Low Refractive Index Layer] The low refractive index layer is a layer having a refractive index lower than that of the transparent substrate, and is located on the opposite side to a display element (e.g., a liquid crystal display element, an EL display element) when the antireflection member is incorporated into an image display device. The low refractive index layer contains a binder resin, hollow silica particles, and non-hollow silica particles.

[0061] <Binder resin> The binder resin includes a cured product of a curable resin composition such as a thermosetting resin composition or an ionizing radiation curable resin composition. Among these, a cured product of a curable resin composition is preferable from the viewpoint of scratch resistance. In addition, examples of the curable resin composition include a thermosetting resin composition and an ionizing radiation curable resin composition, and an ionizing radiation curable resin composition is preferable from the viewpoint of scratch resistance. That is, it is optimal for the binder resin to include a cured product of an ionizing radiation curable resin composition.

[0062] The thermosetting resin composition is a composition that contains at least a thermosetting resin, and is a resin composition that is cured by heating. Examples of the thermosetting resin include acrylic resin, urethane resin, phenol resin, urea melamine resin, epoxy resin, unsaturated polyester resin, silicone resin, etc. In the thermosetting resin composition, a curing agent is added to the curable resin as required.

[0063] The ionizing radiation curable resin composition is a composition containing a compound having an ionizing radiation curable functional group (hereinafter, also referred to as "ionizing radiation curable compound"). Examples of the ionizing radiation curable functional group include ethylenically unsaturated bond groups such as (meth)acryloyl group, vinyl group, and allyl group, as well as epoxy group and oxetanyl group. The ionizing radiation curable compound preferably has two or more ionizing radiation curable functional groups. As the ionizing radiation curable compound, a compound having an ethylenically unsaturated bond group is preferred, and among them, a (meth)acrylate-based compound having a (meth)acryloyl group is more preferred. Hereinafter, a (meth)acrylate compound having four or more ethylenically unsaturated bond groups is referred to as a "polyfunctional (meth)acrylate compound", and a (meth)acrylate compound having two or three ethylenically unsaturated bond groups is referred to as a "low-functional (meth)acrylate compound".

[0064] As the (meth)acrylate-based compound, both monomers and oligomers can be used. In particular, from the viewpoint of suppressing shrinkage unevenness during curing and facilitating smoothing of the uneven shape of the low refractive index layer surface, it is more preferable that the ionizing radiation curable compound contains a low-functional (meth)acrylate-based compound. In addition, the ratio of the low-functional (meth)acrylate-based compound in the ionizing radiation curable compound is preferably 60% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, even more preferably 95% by mass or more, and most preferably 100% by mass. In addition, from the viewpoint of suppressing the above-mentioned shrinkage unevenness during curing and facilitating smoothing of the uneven shape of the low refractive index layer surface, it is preferable that the low-functional (meth)acrylate-based compound is a (meth)acrylate-based compound having two ethylenically unsaturated bond groups. Even when the ionizing radiation curable compound contains a large amount of a polyfunctional (meth)acrylate compound, the uneven shape of the surface of the low refractive index layer can be easily smoothed by appropriately adjusting the type of solvent and drying conditions, as described below.

[0065] Among the (meth)acrylate compounds, examples of bifunctional (meth)acrylate compounds include isocyanuric acid di(meth)acrylate, polyalkylene glycol di(meth)acrylates such as ethylene glycol di(meth)acrylate, polyethylene glycol diacrylate, and polybutylene glycol di(meth)acrylate, bisphenol A tetraethoxydiacrylate, bisphenol A tetrapropoxydiacrylate, and 1,6-hexanediol diacrylate. Examples of trifunctional (meth)acrylate compounds include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, and isocyanuric acid modified tri(meth)acrylate. Examples of polyfunctional (meth)acrylate compounds having 4 or more functional groups include pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and dipentaerythritol tetra(meth)acrylate. These (meth)acrylate compounds may be modified as described below.

[0066] Examples of the (meth)acrylate oligomer include acrylate polymers such as urethane (meth)acrylate, epoxy (meth)acrylate, polyester (meth)acrylate, and polyether (meth)acrylate. The urethane (meth)acrylate can be obtained, for example, by reacting a polyhydric alcohol and an organic diisocyanate with a hydroxy (meth)acrylate. In addition, preferred epoxy (meth)acrylates are (meth)acrylates obtained by reacting a tri- or higher functional aromatic epoxy resin, alicyclic epoxy resin, aliphatic epoxy resin, or the like with (meth)acrylic acid, (meth)acrylates obtained by reacting a di- or higher functional aromatic epoxy resin, alicyclic epoxy resin, aliphatic epoxy resin, or the like with a polybasic acid and (meth)acrylic acid, and (meth)acrylates obtained by reacting a di- or higher functional aromatic epoxy resin, alicyclic epoxy resin, aliphatic epoxy resin, or the like with a phenol and (meth)acrylic acid.

[0067] In addition, the (meth)acrylate compound may have a part of its molecular skeleton modified in order to suppress uneven shrinkage caused by crosslinking. For example, compounds modified with ethylene oxide, propylene oxide, caprolactone, isocyanuric acid, alkyl, cyclic alkyl, aromatic, bisphenol, etc. may also be used. In particular, in order to increase the affinity with silica particles to suppress particle aggregation and to facilitate the C / Si ratio being within the above range, the (meth)acrylate compound is preferably modified with an alkylene oxide such as ethylene oxide or propylene oxide. The proportion of the alkylene oxide-modified (meth)acrylate compound in the ionizing radiation curable compound is preferably 60% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, even more preferably 95% by mass or more, and most preferably 100% by mass. Moreover, the alkylene oxide-modified (meth)acrylate compound is preferably a low-functionality (meth)acrylate compound, and more preferably a (meth)acrylate compound having two ethylenically unsaturated bond groups.

[0068] Examples of the (meth)acrylate-based compound having two ethylenically unsaturated bond groups modified with alkylene oxide include bisphenol F alkylene oxide modified di(meth)acrylate, bisphenol A alkylene oxide modified di(meth)acrylate, isocyanuric acid alkylene oxide modified di(meth)acrylate, and polyalkylene glycol di(meth)acrylate, among which polyalkylene glycol di(meth)acrylate is preferred. The average repeating unit of the alkylene glycol contained in the polyalkylene glycol di(meth)acrylate is preferably 3 to 5. The alkylene glycol contained in the polyalkylene glycol di(meth)acrylate is preferably ethylene glycol and / or polyethylene glycol. Examples of the (meth)acrylate compound having three ethylenically unsaturated bond groups modified with an alkylene oxide include trimethylolpropane alkylene oxide modified tri(meth)acrylate and isocyanuric acid alkylene oxide modified tri(meth)acrylate. The above ionizing radiation curable resins may be used alone or in combination of two or more.

[0069] When the ionizing radiation curable resin is an ultraviolet ray curable resin, the coating liquid for forming the antiglare layer preferably contains additives such as a photopolymerization initiator and a photopolymerization accelerator. The photopolymerization initiator may be one or more selected from acetophenone, benzophenone, α-hydroxyalkylphenone, Michler's ketone, benzoin, benzil dimethyl ketal, benzoyl benzoate, α-acyloxime ester, α-aminoalkylphenone, thioxanthones, and the like. The photopolymerization accelerator can reduce polymerization inhibition caused by air during curing and increase the curing speed, and examples of the accelerator include one or more types selected from p-dimethylaminobenzoic acid isoamyl ester, p-dimethylaminobenzoic acid ethyl ester, etc.

[0070] The binder resin may further contain additives such as an antistatic agent, an antioxidant, a surfactant, a dispersant, and an ultraviolet absorber. The additives for the curable resin composition forming the binder resin are not particularly limited, but preferably contain a silicone-based leveling agent (silicone-based compound). By containing the silicone-based leveling agent, the surface of the low refractive index layer can be made smoother. Furthermore, the surface of the low refractive index layer can be made good in slipperiness and antifouling properties (ease of wiping off fingerprints, large contact angle with pure water and hexadecane). Depending on the processing conditions, a fluorine-based leveling agent, a mixture of a fluorine-based and a silicone-based leveling agent, or a mixture of multiple fluorine-silicone leveling agents can also be used.

[0071] However, in consideration of the scratch resistance (steel wool resistance and oil dust resistance) of the low refractive index layer, it may be preferable that the curable resin composition forming the binder resin does not contain a fluorine-containing compound such as a fluorine-containing oligomer and / or monomer having an ionizing radiation curable functional group (particularly when high-speed mass production processing is required). In addition, since there is a possibility of generating hydrofluoric acid when burned, such as when disposing of the product, it is particularly preferable not to contain a fluorine-based leveling agent (fluorine-containing compound) as an additive. A fluorine-based leveling agent may be used when the compatibility between a silicone-based leveling agent and a binder resin is poor.

[0072] <Silica particles> In the present invention, the low refractive index layer preferably contains hollow silica particles and non-hollow silica particles. Hollow silica particles refer to particles that have a shell layer made of silica, the inside of the particle surrounded by the shell layer is hollow, and the inside of the cavity contains air.Hollow silica particles are particles that contain air, and the refractive index is reduced in proportion to the occupancy rate of gas compared to the refractive index of silica itself.Non-hollow silica particles are particles that are not hollow like hollow silica particles.Non-hollow silica particles are, for example, solid silica particles. The shape of the hollow silica particles and non-hollow silica particles is not particularly limited, and may be a perfect sphere, a spheroid, or a nearly spherical shape such as a polyhedron that can approximate a sphere, etc. Among these, in consideration of scratch resistance, a perfect sphere, a spheroid, or a nearly spherical shape is preferable.

[0073] Since hollow silica particles contain air inside, they play a role in lowering the refractive index of the entire low refractive index layer. By using hollow silica particles with a large particle size and a high ratio of air, the refractive index of the low refractive index layer can be further lowered. On the other hand, hollow silica particles tend to have poor mechanical strength. In particular, when hollow silica particles with a large particle size and a high ratio of air are used, the scratch resistance of the low refractive index layer tends to be easily reduced. The non-hollow silica particles, when dispersed in the binder resin, play a role in improving the scratch resistance of the low refractive index layer.

[0074] In order to disperse the hollow silica particles and non-hollow silica particles uniformly in the resin in the thickness direction while the hollow silica particles are present at a high concentration in the binder resin, it is preferable to set the average particle size of the hollow silica particles and the average particle size of the non-hollow silica particles so that the hollow silica particles are close to each other and the non-hollow particles can be inserted between the hollow silica particles. Specifically, the ratio of the average particle size of the non-hollow silica particles to the average particle size of the hollow silica particles is preferably 0.29 or less, more preferably 0.20 or less. In addition, the ratio of the average particle sizes is preferably 0.05 or more. In consideration of optical properties and mechanical strength, the average particle size of the hollow silica particles is preferably 50 nm or more and 100 nm or less, more preferably 60 nm or more and 80 nm or less. In consideration of dispersibility while preventing aggregation of the non-hollow silica particles, the average particle size of the non-hollow silica particles is preferably 5 nm or more and 20 nm or less, more preferably 10 nm or more and 15 nm or less.

[0075] The "average particle size" in the present invention can be calculated by the following steps (1) to (3). (1) A cross section of an antireflection member containing particles is imaged by a TEM or STEM. The accelerating voltage of the TEM or STEM is preferably 10 kv to 30 kV, and the magnification is preferably 50,000 to 300,000. (2) Randomly extract 10 particles from the observed image, and calculate the particle diameter of each particle. The particle diameter is measured as the distance between two parallel lines that is the maximum distance between the two lines when the cross section of the particle is sandwiched between the two lines. (3) Repeat the same procedure five times on a separate image of the same sample, and use the number average of a total of 50 particles as the average particle size.

[0076] The surfaces of the hollow silica particles and non-hollow silica particles are preferably coated with a silane coupling agent, and it is more preferable to use a silane coupling agent having a (meth)acryloyl group or an epoxy group. By subjecting the silica particles to a surface treatment with a silane coupling agent, the affinity between the silica particles and the binder resin is improved, and the silica particles are less likely to aggregate, which makes it easier for the silica particles to be dispersed uniformly.

[0077] Examples of silane coupling agents include 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-di methyl-butylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, tris-(trimethoxysilylpropyl)isocyanurate, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-isocyanatopropyltriethoxysilane, methyltrimethoxysilane, dimethyldimethoxysilane, phenyltrimethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, phenyltriethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, hexyltrimethoxysilane, hexyltriethoxysilane, octyltriethoxysilane, decyltrimethoxysilane, 1,6-bis(trimethoxysilyl)hexane, trifluoropropyltrimethoxysilane, vinyltrimethoxysilane and vinyltriethoxysilane. In particular, it is preferable to use one or more selected from 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, and 3-methacryloxypropyltriethoxysilane.

[0078] The higher the content of hollow silica particles, the higher the filling rate of hollow silica particles relative to the binder resin, and the lower the refractive index of the low refractive index layer. On the other hand, if the content of hollow silica particles relative to the binder resin is too high, the number of hollow silica particles exposed from the binder resin increases, and the binder resin that bonds between the particles decreases. Therefore, the hollow silica particles tend to be easily damaged or fall off, and the mechanical strength of the low refractive index layer, such as scratch resistance, tends to decrease. Therefore, the content of hollow silica particles is preferably 100 parts by mass or more relative to 100 parts by mass of binder resin, and more preferably 150 parts by mass or more. In addition, the content of hollow silica particles is preferably 400 parts by mass or less relative to 100 parts by mass of binder resin, and more preferably 300 parts by mass or less.

[0079] When the content of non-hollow silica particles is small, the presence of non-hollow silica particles on the surface of the low refractive index layer may not affect the hardness increase. In addition, when the content of non-hollow silica particles is large, the effect of shrinkage unevenness caused by polymerization of the binder resin can be reduced, and the unevenness occurring on the surface of the low refractive index layer after the resin is cured can be reduced. On the other hand, when the content of non-hollow silica particles is too large, the non-hollow silica aggregates, causing shrinkage unevenness of the binder resin, and the unevenness of the surface becomes large. The content of non-hollow silica particles is preferably 90 parts by mass or more, more preferably 100 parts by mass or more, relative to 100 parts by mass of the binder resin. In addition, the content of non-hollow silica particles is preferably 200 parts by mass or less, more preferably 150 parts by mass or less, relative to 100 parts by mass of the binder resin.

[0080] By incorporating hollow silica particles and non-hollow silica particles in the binder resin in the above ratio, even if a fluorine-containing compound such as a fluorine-based leveling agent is contained in the hard coat layer or the high refractive index layer, the fluorine-containing compound is not detected on the surface of the low refractive index layer. This is presumably because the silica particles are uniformly dispersed in the binder resin at a high concentration, and thus the silica particles inhibit the diffusion of the fluorine-based leveling agent.

[0081] In addition, by adding hollow silica particles and non-hollow silica particles to the binder resin in the above ratio, the gas barrier properties of the antireflection member itself can be improved, which is presumably because the silica particles are uniformly dispersed at a high filling rate, thereby inhibiting the permeation of gases, etc. In addition, cosmetics such as sunscreens and hand creams may contain low-volatility low-molecular-weight polymers. By improving the barrier properties of the low-refractive index layer, it is possible to prevent the low-molecular-weight polymer from penetrating into the low-refractive index layer. This makes it possible to prevent problems (e.g., abnormal appearance) caused by the low-molecular-weight polymer remaining in the low-refractive index layer for a long period of time.

[0082] The thickness of the low refractive index layer is not particularly limited as long as it is 50 nm or more (greater than the average particle size of hollow silica), but is preferably 80 to 120 nm, more preferably 85 to 110 nm, and even more preferably 90 to 105 nm. The refractive index of the low refractive index layer is preferably 1.40 or less, more preferably 1.35 or less. By making the refractive index of the low refractive index layer 1.40 or less, the reflectance of the surface of the low refractive index layer is prevented from increasing, and visibility can be easily improved. The lower limit of the refractive index of the low refractive index layer is about 1.10. In this specification, the refractive index refers to the refractive index at a wavelength of 589.3 nm.

[0083] [Hard Coat Layer] When the transparent substrate is made of plastic, it is preferable to provide a hard coat layer between the low refractive index layer and the transparent substrate. By providing the hard coat layer, the indentation hardness and recovery rate can be improved. The hard coat layer contains a cured product of a curable resin composition such as a thermosetting resin composition or an ionizing radiation curable resin composition. As the curable resin, the same curable resin as that for the low refractive index layer can be used.

[0084] When the ionizing radiation curable compound is an ultraviolet ray curable compound, the ionizing radiation curable composition preferably contains additives such as a photopolymerization initiator and a photopolymerization accelerator. As the photopolymerization initiator and the photopolymerization accelerator, the same materials as those for the low refractive index layer can be used.

[0085] The hard coat layer preferably further contains a leveling agent as an additive. By adding a leveling agent, the coating film that becomes the hard coat layer can be formed uniformly. As the leveling agent, a fluorine-based leveling agent, a silicone-based leveling agent, a fluorine-silicone-based leveling agent, or a mixture of these can be used. In the present invention, even if a fluorine-based leveling agent is contained in the hard coat layer, the silica particles in the low refractive index layer inhibit the diffusion of the fluorine-based leveling agent, and it is easy to suppress the migration of the fluorine-based leveling agent to the surface of the low refractive index layer. The hard coat layer may further contain additives such as an antistatic agent, an antioxidant, a surfactant, a dispersant, and an ultraviolet absorbing agent.

[0086] The thickness of the hard coat layer is preferably 0.1 to 100 μm, more preferably 0.5 to 20 μm, and further preferably 1 to 10 μm. By setting the thickness of the hard coat layer within the above range, it is possible to improve scratch resistance and easily suppress the occurrence of cracks during processing such as cutting.

[0087] The refractive index of the hard coat layer is preferably adjusted within the range of 1.45 to 1.70. Furthermore, when the antireflection member has a high refractive index layer described later, the refractive index of the hard coat layer is preferably lower than that of the high refractive index layer, more preferably 1.50 to 1.65, and even more preferably 1.55 to 1.60. If the refractive index of the hard coat layer is within this range, the hard coat layer serves as a medium refractive index layer, and interference action by the three layers of the hard coat layer (medium refractive index layer), high refractive index layer, and low refractive index layer becomes possible, so that the reflectance can be further reduced. In addition, when there is another layer (a light-transmitting substrate or another layer constituting the resin layer) between the hard coat layer and the adherend, it is preferable to reduce the difference in refractive index between the other layer and the hard coat layer from the viewpoint of suppressing interference fringes. In this specification, the refractive index can be calculated, for example, by fitting a reflection spectrum measured by a reflectance photometer to a reflection spectrum calculated from an optical model of a multilayer thin film using Fresnel coefficients.

[0088] As a means for imparting the role of a medium refractive index layer to the hard coat layer, there are a means for blending a resin having a high refractive index into the hard coat layer coating liquid and a means for blending particles having a high refractive index. Examples of the resin having a high refractive index include the above-mentioned thermosetting resin or ionizing radiation curable compound into which a group containing sulfur, phosphorus, or bromine, an aromatic ring, etc. are introduced. Examples of the particles having a high refractive index include the same particles as those used in the high refractive index layer described later.

[0089] [High Refractive Index Layer] The high refractive index layer is a layer having a refractive index higher than that of the hard coat layer, and contains high refractive index particles and a binder resin.

[0090] The high refractive index layer contains, as a binder resin, a cured product of a curable resin composition such as a thermosetting resin composition or an ionizing radiation curable resin composition. As the curable resin composition, the same ones as those exemplified for the low refractive index layer can be used, and an ionizing radiation curable resin composition is preferable.

[0091] When the ionizing radiation curable compound is an ultraviolet ray curable compound, the ionizing radiation curable composition preferably contains additives such as a photopolymerization initiator and a photopolymerization accelerator. As the photopolymerization initiator and the photopolymerization accelerator, the same materials as those for the low refractive index layer can be used.

[0092] The high refractive index layer preferably further contains a leveling agent as an additive. By adding a leveling agent, the coating film that becomes the high refractive index layer can be formed uniformly. As the leveling agent, a fluorine-based leveling agent, a silicone-based leveling agent, a fluorine-silicone-based leveling agent, or a mixture of each of them can be used. In the present invention, even if a fluorine-based leveling agent is contained in the high refractive index layer, the silica particles in the low refractive index layer inhibit the diffusion of the fluorine-based leveling agent, and it is easy to suppress the migration of the fluorine-based leveling agent to the surface of the low refractive index layer. The high refractive index layer may further contain additives such as an antistatic agent, an antioxidant, a surfactant, a dispersant, and an ultraviolet absorbing agent.

[0093] Examples of high refractive index particles include antimony pentoxide, zinc oxide, titanium oxide, cerium oxide, tin-doped indium oxide, antimony-doped tin oxide, yttrium oxide, and zirconium oxide. The average particle size of the high refractive index particles is preferably 5 nm or more and 200 nm or less, more preferably 5 nm or more and 100 nm or less, and even more preferably 10 nm or more and 80 nm or less.

[0094] From the viewpoint of achieving a balance between increasing the refractive index of the coating film and the strength of the coating film, the content of the high refractive index particles is preferably from 100 parts by mass to 2,500 parts by mass, more preferably from 300 parts by mass to 2,200 parts by mass, and even more preferably from 500 parts by mass to 2,000 parts by mass, relative to 100 parts by mass of the binder resin.

[0095] In particular, by providing a high refractive index layer in which high-hardness particles such as zirconium oxide, antimony pentoxide, titanium oxide, etc. are dispersed in a binder resin at a high concentration as high refractive index particles, the indentation hardness and recovery rate of the low refractive index layer can be improved. In consideration of improving the indentation hardness and recovery rate of the low refractive index layer, the content of the high refractive index particles is preferably 1000 parts by mass or more and 2000 parts by mass or less, and more preferably 1500 parts by mass or more and 2000 parts by mass or less.

[0096] The refractive index of the high refractive index layer is preferably 1.55 or more and 1.85 or less, and more preferably 1.56 or more and 1.75 or less. The thickness of the high refractive index layer is preferably 200 nm or less, and more preferably 50 nm or more and 180 nm or less.

[0097] [Method for manufacturing anti-reflection member] The hard coat layer, low refractive index layer, and high refractive index layer of the antireflection member of the present invention can be formed by a wet method in which a coating liquid containing the components constituting each layer is applied onto a transparent substrate, dried, and cured, or by a transfer method in which each layer formed on a substrate by a wet method is transferred, etc. The coating liquid contains a solvent, solids constituting each layer, and additives such as a polymerization initiator.

[0098] When forming by a wet method, first, a coating liquid for forming a low refractive index layer is applied onto a transparent substrate, and then dried and cured to form a low refractive index layer. When providing a hard coat layer, a coating liquid for forming a hard coat layer is applied onto a transparent substrate, and then dried and cured to form a hard coat layer, and then a low refractive index layer is formed in the same manner as above. When providing a hard coat layer and a high refractive index layer, a coating liquid for forming a high refractive index layer is applied onto the hard coat layer, and then dried and cured to form a hard coat layer and a high refractive index layer, and then a low refractive index layer is formed in the same manner as above. Note that the hard coat layer and the high refractive index layer may be in a semi-cured state (not completely cured state) and then completely cured when the low refractive index layer is formed.

[0099] A solvent is usually used in the coating liquid for forming the low refractive index layer in order to adjust the viscosity and to make each component soluble or dispersible. Examples of the solvent include ketones (acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, etc.), ethers (dioxane, tetrahydrofuran, etc.), aliphatic hydrocarbons (hexane, etc.), alicyclic hydrocarbons (cyclohexane, etc.), aromatic hydrocarbons (toluene, xylene, etc.), halogenated carbons (dichloromethane, dichloroethane, etc.), esters (methyl acetate, ethyl acetate, butyl acetate, etc.), alcohols (butanol, cyclohexanol, etc.), cellosolves (methyl cellosolve, ethyl cellosolve, etc.), cellosolve acetates, sulfoxides (dimethyl sulfoxide, etc.), glycol ethers (1-methoxy-2-propyl acetate, etc.), amides (dimethylformamide, dimethylacetamide, etc.), and mixtures of these may also be used.

[0100] If the solvent evaporates too quickly, the solvent will convect violently when the coating liquid for forming a low refractive index layer is dried. Therefore, even if the silica particles in the coating liquid are in a uniformly dispersed state, the state of uniform dispersion is likely to be lost due to the violent convection of the solvent during drying. For this reason, it is preferable that the solvent contains one with a slow evaporation rate. Specifically, it is preferable that the solvent contains a solvent with a relative evaporation rate (relative evaporation rate when the evaporation rate of n-butyl acetate is set to 100) of 70 or less, and more preferably a solvent with a relative evaporation rate of 30 to 60. In addition, the solvent with a relative evaporation rate of 70 or less is preferably 10 to 50 mass % of the total solvent, and more preferably 20 to 40 mass %. Examples of relative evaporation rates for slow evaporating solvents are isobutyl alcohol 64, 1-butanol 47, 1-methoxy-2-propyl acetate 44, ethyl cellosolve 38, and cyclohexanone 32. The remaining solvent (solvent other than the solvent having a slow evaporation rate) is preferably one having excellent resin solubility. The remaining solvent is preferably one having a relative evaporation rate of 100 or more.

[0101] In order to suppress the convection of the solvent during drying and to improve the dispersibility of the silica particles, it is preferable that the drying temperature during the formation of the low refractive index layer is as low as possible. The drying temperature can be appropriately set in consideration of the type of solvent, the dispersibility of the silica particles, the production speed, etc.

[0102] The method for curing each layer may be a method of irradiating with ionizing radiation such as ultraviolet light or electron beams, or a method of curing by heating. In consideration of productivity, etc., it is preferable to adopt curing by ionizing radiation.

[0103] [Size, shape, etc. of anti-reflection member] The antireflection member may be in the form of a sheet cut to a predetermined size, or in the form of a roll obtained by winding a long sheet into a roll. The size of the sheet is not particularly limited, but the maximum diameter is about 2 to 500 inches. The "maximum diameter" refers to the maximum length when any two points on the antireflection member are connected. For example, when the antireflection member is rectangular, the diagonal line of the area is the maximum diameter. When the antireflection member is circular, the diameter is the maximum diameter. The width and length of the roll are not particularly limited, but generally, the width is about 500 to 3000 mm, and the length is about 100 to 5000 m. The antireflection member in the form of a roll can be cut into sheets according to the size of an image display device or the like. When cutting, it is preferable to remove the ends of the roll, which have unstable physical properties. The shape of the sheet is not particularly limited, and may be, for example, a polygon (triangle, square, pentagon, etc.), a circle, or a random, indefinite shape. More specifically, when the anti-reflection member is a square, the aspect ratio is not particularly limited as long as it does not cause any problems as a display screen. For example, the aspect ratio may be 1:1, 4:3, 16:10, 16:9, 2:1, etc.

[0104] [Polarizing plate] The polarizing plate of the present invention comprises a transparent protective plate, a polarizer and a transparent protective plate in this order, and at least one of the two transparent protective plates is the above-mentioned antireflection member.

[0105] When only one of the two transparent protective plates is the above-mentioned antireflection member, examples of the other transparent protective plate include those exemplified as the transparent base material described above.

[0106] Examples of polarizers include sheet-type polarizers such as polyvinyl alcohol films, polyvinyl formal films, polyvinyl acetal films, and saponified ethylene-vinyl acetate copolymer films dyed with iodine or the like and stretched, wire-grid-type polarizers made of a large number of metal wires arranged in parallel, coating-type polarizers coated with lyotropic liquid crystal or a dichroic guest-host material, and multilayer thin-film-type polarizers. These polarizers may be reflective polarizers that have the function of reflecting polarized components that are not transmitted.

[0107] [Image display device] The image display device of the present invention has the above-mentioned antireflection member on a display element. In this case, the antireflection member is arranged so that the transparent base material is located on the display element side and the low refractive index layer is located on the user side of the image display device. The display element and the antireflection member are preferably laminated via an adhesive layer. Examples of the display element include a liquid crystal display element, an EL display element, a plasma display element, and an electronic paper element.

[0108] By providing the above-mentioned antireflection member, the image display device of the present invention has an extremely low reflectance and excellent visibility, and also has excellent resistance to not only steel wool but also oil dust.

[0109] [Anti-reflective article] The antireflective article of the present invention has the above-mentioned antireflective member on a member. In this case, the antireflective member is arranged so that the transparent substrate is located on the member side and the low refractive index layer is located on the user side of the article. The member and the antireflective member are preferably laminated via an adhesive layer.

[0110] Examples of the member include an instrument panel, a clock, a showcase, a show window, and a window. That is, the article of the present invention includes an instrument panel, a clock, a showcase, a show window, and a window in which the release layer of the low reflection member is arranged so as to face the surface. The member may be transparent or opaque, and the color tone is not particularly limited. EXAMPLES

[0111] The present invention will be specifically described below with reference to examples and comparative examples. Note that the present invention is not limited to the embodiments described in the examples.

[0112] 1. Evaluation and measurement The following measurements and evaluations were carried out on the antireflection members obtained in the Examples and Comparative Examples. The results are shown in Tables 1 and 2. Unless otherwise specified and unless the test was carried out in a specific environment, the atmosphere during each measurement and evaluation was set to a temperature of 23±5°C and a relative humidity of 40 to 65%, and the target sample was exposed to the atmosphere for 30 minutes or more before each measurement and evaluation.

[0113] 1-1. Reflectance (visible reflectance Y value) Samples (5 cm × 5 cm) were prepared by bonding a black plate (manufactured by Kuraray, product name: COMOGLAS DFA2CG 502K (black) series, thickness 2 mm) to the transparent substrate side of the antireflection members of the Examples and Comparative Examples via a 25 μm-thick transparent adhesive layer (manufactured by PANAC Corporation, product name: PANACLEAN PD-S1). When the direction perpendicular to the surface of the low refractive index layer of the anti-reflection member was defined as 0 degrees, light was incident on the sample from a direction of 5 degrees, and the reflectance of the sample (luminous reflectance Y value) was measured based on the specularly reflected light of the incident light. The reflectance was measured using a spectroscopic reflectance meter (Shimadzu Corporation, product name: UV-2450) under conditions of a viewing angle of 2 degrees, C light source, and wavelength range of 380 to 780 nm, and then the value indicating the visual reflectance calculated using software (built-in UVPC color measurement Version 3.12) that converts it into the brightness perceived by the human eye was obtained as the reflectance. The average value of the reflectance at 14 points for each sample was taken as the reflectance of each sample.

[0114] 1-2.XPS analysis A measuring piece was cut out from the anti-reflection member of each example and comparative example. Using an X-ray photoelectron spectrometer, the X-ray photoelectron spectrum of the C1s orbital, O1s orbital, Si2p orbital, and F1s orbital of the low refractive index layer surface of each measuring piece was measured under the conditions described below. Peak separation was performed for each X-ray photoelectron spectrum to determine the ratio of C element, O element, F element, and Si element. In addition, from the X-ray photoelectron spectrum of the Si2p orbital, the inorganic component (silica) and the organic component (silicone) were peak-separated to determine the ratio of Si element belonging to silica particles (hollow silica particles and non-hollow silica particles) ("inorganic Si" in the table). Measurement was performed at 14 points for each sample, and further analysis was performed with the number of samples n=2. The average was taken as the element ratio of each example and comparative example. In addition, from the obtained element ratio, the ratio of C element (C / Si) was calculated when the ratio of Si element belonging to silica particles obtained above was converted to 100 atomic %. In Tables 1 and 2, elements other than the Si element derived from inorganic components (inorganic Si element), the C element, and the F element, such as the O element, are listed as "other elements," and the total ratio of these elements is shown. <Measurement> Equipment: Kratos AXIS-NOVA X-ray source: AlKα X-ray power: 150W Emission current: 10mA Acceleration voltage: 15 kV Measurement area: 300×700μm

[0115] 1-3.Surface roughness Using the Atomic Force Microscope (AFM) SPM-9600 manufactured by Shimadzu Corporation, the shape of the surface of the low refractive index layer was measured using the samples of the examples and comparative examples prepared in the measurement of 1-1 in the On-Line (measurement) mode in the SPM Manager software. The measurement conditions are shown below. Then, using the Off-Line (analysis) mode, tilt correction processing was performed to obtain a grayscale image when the height: 0 nm was black and the height: 100 nm or more was white. Note that the lowest point within the measurement range was defined as "height 0 nm". The obtained AFM images were analyzed to obtain the Rz (maximum height roughness) and Ra (arithmetic mean roughness) of each sample. The average values of Rz and Rz / Ra at 14 locations for each sample were evaluated. <AFM Measurement Conditions> Measurement Mode: Phase Scanning Range: 5 μm × 5 μm Scanning Speed: 0.8 - 1 Hz Number of Pixels: 512 × 512 Cantilever Used: NCHR manufactured by Nanoworld (Resonance Frequency: 320 kHz, Spring Constant 42 N / m) <AFM Analysis Conditions> Tilt Correction: Line Fit

[0116] 1-4. Steel Wool Resistance Test The antireflection member evaluated in 1-1 was bonded to the base of a Kagakuhin wear testing machine (manufactured by Tester Sangyo Co., Ltd., product name "AB-301") with the low refractive index layer on the upper surface. Steel wool #0000 (manufactured by Nippon Steel Wool Co., Ltd., product name "Bonster B-204") was set and brought into contact with the surface of the low refractive index layer, and the steel wool was reciprocated 10 times while applying a load at a moving speed of 100 mm / second and a moving distance of 200 mm in one reciprocation (one-way moving distance of 100 mm). The contact area between the steel wool and the low refractive index layer was 1 cm 2The test environment was a temperature of 23±1°C and a relative humidity of 50±5%, unless otherwise specified. The Bonstar B-204 mentioned above is a commercial size with a width of approximately 390 mm, length of approximately 75 mm, and thickness of approximately 110 mm. An appropriate amount was torn off from this (do not cut with a blade, as cutting would cause the cross section of the steel wool fibers to protrude) and rolled uniformly until there were no unusual protruding steel wool parts. When a load of 1000 g was applied, the contact area was 1 cm2. 2 Set the thickness of the steel wool to 20 mm. Thereafter, each anti-reflection member was observed with the naked eye under fluorescent lamps (three-wavelength fluorescent lamps manufactured by Panasonic Corporation, model number: FHF32EX-NH, illuminance on the sample was 800 to 1200 Lx, observation distance 30 cm) and under LED lighting (LED light manufactured by Gentos Corporation, model number: TX-850Re, illuminance on the sample was 4000 to 6000 Lx, observation distance 30 cm), and the number of scratches was evaluated. Steel wool resistance was evaluated as the maximum load per unit area (g / cm2) when no scratches were observed (0 scratches) after the test. 2 For each of the Examples and Comparative Examples, the test was carried out twice (n=2), and the average was taken as the steel wool resistance of each of the Examples and Comparative Examples.

[0117] 1-5.Oil dust resistance test A test liquid was prepared by mixing AC dust (ISO12103-1, A2 (Fine)) and olive oil (CAS No. 8001-25-0) at a 1 / 1 (weight ratio). A cloth (manufactured by AS ONE Corporation, product name "ASPURE PROPLEA II") was folded into eight layers and firmly attached to the tip of a rod-shaped metal member (rod-shaped end surface shaped as a 1 cm x 1 cm square) with a rubber band. The side of the rod-shaped metal member to which the cloth was attached was immersed in the above test liquid, and 5 g of the above test liquid was evenly applied to the end surface of the cloth to obtain a rod-shaped metal member for rubbing. The anti-reflection members of the Examples and Comparative Examples were attached to a test stand so that the low refractive index layer was on the upper surface. A weight was attached to the rod-shaped metal member for rubbing, and the cloth side of the rod-shaped metal member was brought into contact with the surface of the low refractive index layer, and the weight was moved back and forth 10 times at a moving speed of 100 mm / sec and a moving distance of 200 mm per round trip (one-way moving distance 100 mm). The contact area between the cloth and the low refractive index layer was approximately 1 cm2, which is roughly equal to the area of ​​the end face of the rod-shaped metal member. 2 Unless otherwise specified, the test environment was set to a temperature of 23±1°C and a relative humidity of 50±5%. Thereafter, the anti-reflection members of the examples and comparative examples were observed with the naked eye under fluorescent lamps (three-wavelength fluorescent lamps manufactured by Panasonic Corporation, model number: FHF32EX-NH, illuminance on the sample of 800 to 1200 Lx, observation distance of 30 cm) and under LED lighting (LED light manufactured by Gentos Corporation, model number: TX-850Re, illuminance on the sample of 4000 to 6000 Lx, observation distance of 30 cm), and the number of scratches was evaluated. The load was the weight of a weight, and the oil dust resistance was evaluated as the maximum load per unit area (g / cm2) when no scratches were observed after the test (0 scratches). 2 For each of the examples and comparative examples, the test was carried out with n=2, and the average was taken as the oil dust resistance of each of the examples and comparative examples.

[0118] 1-6. Anti-stain properties (fingerprints can be wiped off easily) The pad of a finger was pressed against the surface of the low refractive index layer of the antireflection members of the Examples and Comparative Examples to leave a fingerprint. The fingerprint was then wiped off using a nonwoven fabric (manufactured by Asahi Kasei Corporation, product name: Bencotton), and the number of times it was wiped off until the fingerprint was no longer visible was evaluated. Those whose fingerprints were no longer visible after wiping up to three times were rated "A", those whose fingerprints were no longer visible after wiping four to seven times were rated "B", and those whose fingerprints were still visible after wiping seven times were rated "C".

[0119] 1-7.Indentation hardness For the low refractive index layers of the antireflection members of Examples 1, 6, and 8 and Comparative Examples 1, 3 to 4, load-displacement curves were measured under the following conditions using a TriboIndenter TI950 manufactured by Hysitron. The indentation hardness was obtained from the obtained load-displacement curves using analysis software (TRIBOSCAN) attached to the device. Measurements were performed at 16 points for each sample, and further analysis was performed for the number of samples n=2. The average of the obtained values ​​was taken as the indentation hardness of each Example and Comparative Example.

[0120] <Indentation hardness measurement conditions> Indenter used: Berkovich indenter (TI-0039) -Indentation condition: Displacement control method Maximum indentation depth: 30 nm Load application time: 3 seconds (speed: 10 nm / sec) Hold Time: 5 seconds Loading / unloading time: 3 seconds (speed: 10 nm / sec) Push-in speed: 10nm / sec

[0121] 1-8. Recovery rate For the low refractive index layers of the antireflection members of Examples 1, 6, and 8 and Comparative Examples 1, 3 to 4, load-displacement curves were measured under the following conditions using a TriboIndenter TI950 manufactured by Hysitron. From the load-displacement curves obtained, the recovery rates were calculated. Measurements were performed at 16 points for each sample, and further analysis was performed for the number of samples n=2. The average of the obtained values ​​was taken as the recovery rate for each Example and Comparative Example.

[0122] <Conditions for measuring recovery rate> Indenter used: Berkovich indenter (TI-0039) Pressing conditions: Load control method ·Maximum load: 30μN Load application time: 3 seconds (speed: 10μN / sec) Hold Time: 5 seconds Load unloading time: 3 seconds (speed: 10μN / sec)

[0123] 2. Preparation of Coating Solution A coating solution for forming a hard coat layer having the following formulation was prepared. <Coating solution 1 for forming hard coat layer> 22 parts by weight of ultraviolet-curable acrylate-containing composition (manufactured by Nippon Kayaku Co., Ltd., product name "KAYARAD PET-30", solid content 100%) UV-curable acrylate-containing composition (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., product name "New Frontier R-1403MB", solid content 80%) 17 parts by mass Fluorine-based leveling agent (manufactured by DIC Corporation, product name "Megafac F-568") 1 part by weight ·Photopolymerization initiator (manufactured by IGM Resins, trade name "Omnirad184") 1 part by mass Methyl isobutyl ketone 15 parts by weight Methyl ethyl ketone 44 parts by weight

[0124] <Coating solution 2 for forming hard coat layer> ·Reactive silica fine particles (manufactured by JSR Corporation, "Z7837", product containing 50% solids and 60% reactive silica fine particles) 10 parts by mass Urethane acrylate (Mitsubishi Chemical Corporation, "UV1700B") 5.7 parts by weight ·Photopolymerization initiator (manufactured by IGM Resins, trade name "Omnirad184") 1 part by mass Fluorine-based leveling agent (manufactured by DIC Corporation, product name "Megafac F-568") 1 part by weight Methyl ethyl ketone 3.3 parts by weight Methyl isobutyl ketone 2.3 parts by weight

[0125] A coating solution for forming a high refractive index layer having the following formulation was prepared. <Coating solution 1 for forming high refractive index layer> PETA (manufactured by Nippon Kayaku Co., Ltd., product name "KAYARAD PET-30", solid content 100%) 0.15 parts by weight High refractive index particles (manufactured by Nippon Shokubai Co., Ltd., product name "Zircostar", solid content 70%) 4.5 parts by weight Fluorine-based leveling agent (manufactured by DIC Corporation, product name "Megafac F251") 0.01 parts by weight Photopolymerization initiator (manufactured by IGM Resins, product name "Omnirad127") 0.14 parts by mass Methyl isobutyl ketone 47.6 parts by weight Propylene glycol monomethyl ether 47.6 parts by weight

[0126] <Coating solution 2 for forming high refractive index layer> PETA (manufactured by Nippon Kayaku Co., Ltd., product name "KAYARAD PET-30", solid content 100%) 0.68 parts by weight High refractive index particles (manufactured by JGC Catalysts and Chemicals Co., Ltd., product name "ELCOM V-4564" (containing antimony pentoxide particles), solid content 40.5%) 6.71 parts by weight Fluorine-based leveling agent (manufactured by DIC Corporation, product name "Megafac F251") 2.03 parts by weight Photopolymerization initiator (manufactured by IGM Resins, product name "Omnirad127") 0.05 parts by weight Methyl isobutyl ketone 46.3 parts by weight Propylene glycol monomethyl ether 44.23 parts by weight

[0127] <Coating solution 3 for forming high refractive index layer> 20 parts by weight of ITO fine particle dispersion in ethanol (solid content 20.5 wt%) PETA (manufactured by Nippon Kayaku Co., Ltd., product name "KAYARAD PET-30", solid content 100%) 1 part by weight ITO dispersion aid (phosphate ester type) 0.1 parts by weight ·Photopolymerization initiator (manufactured by IGM Resins, product name "Omnirad184") 0.2 parts by mass Ethanol (adjust the amount added so that the solids concentration is 4% by mass)

[0128] A coating solution for forming a low refractive index layer having the following formulation was prepared. <Coating solution 1 for forming low refractive index layer> The following hollow silica particles and non-hollow silica particles were used. Tables 1 and 2 show the blending amounts (solid content) of hollow silica particles and non-hollow silica particles (solid silica particles) in parts by mass when the binder resin (solid content) is 100 parts by mass. (1) Hollow silica particles Dispersion with 20% solids by mass, surface treated with a silane coupling agent having a methacryloyl group, average particle size 75 nm (2) Non-hollow silica particles Solid silica particle dispersion with 40% solids by mass, surface treated with a silane coupling agent having a methacryloyl group, average particle size 7nm or 12.5nm

[0129] The following binder resins were used. Tables 1 and 2 show the percentages of solid content. (3) Binder resin TEGDA: Polyethylene glycol (n≒4) diacrylate (bifunctional acrylate), manufactured by Toagosei Co., Ltd., product name "M-240" PETA: Pentaerythritol (tri / tetra)acrylate, manufactured by Nippon Kayaku Co., Ltd., product name "KAYARAD PET-30" DPHA: Dipentaerythritol (hexa / penta)acrylate, manufactured by Nippon Kayaku Co., Ltd., product name "KAYARAD DPHA" Fluorine-containing compound: fluorine-containing compound having a (meth)acryloyl group, a reactive silane unit, and a silane unit having a perfluoropolyether group, solid content 20% by mass, solvent: methyl isobutyl ketone, manufactured by Shin-Etsu Chemical Co., Ltd., product name "X-71-1203M"

[0130] The following photopolymerization initiators and leveling agents were used: Tables 1 and 2 show the percentages of solid content when the binder resin (solid content) is taken as 100 parts by mass. (4) Photopolymerization initiator Manufactured by IGM Resins, product name “Omnirad127” 4.3 parts by mass (5) Leveling agent (a) Silicone-based (Si-based-1) leveling agent: Shin-Etsu Chemical Co., Ltd., product name "KP-420" 13 parts by mass (b) Fluorine-based leveling agent 1 (F-1): 13 parts by mass of "X-71-1203M" manufactured by Shin-Etsu Chemical Co., Ltd. (c) Fluorine-based leveling agent 2 (F-2): 5 parts by weight of "Megafac RS-81" manufactured by DIC Corporation

[0131] In Examples 1 to 8 and Comparative Examples 1 and 2, methyl isobutyl ketone and 1-methoxy-2-propyl acetate were used as the solvent. The mixing ratio was methyl isobutyl ketone / 1-methoxy-2-propyl acetate=68 / 32 (mass ratio). The amount of the mixed solvent was 14,867 parts by mass per 100 parts by mass of the binder resin (solid content). In Comparative Examples 3 and 4, methyl isobutyl ketone and 2-methoxy-1-methylethyl acetate were used as the solvent. The mixing ratio was methyl isobutyl ketone / 2-methoxy-1-methylethyl acetate=89 / 11 (mass ratio). The blending amount of the mixed solvent was 8,667 parts by mass per 100 parts by mass of the binder resin (solid content).

[0132] <Coating solution 2 for forming low refractive index layer> The following hollow silica particles and non-hollow silica particles were used. Table 2 shows the blending amounts (solid content) of hollow silica particles and non-hollow silica particles (solid silica particles) in parts by mass when the binder resin (solid content) is 100 parts by mass. (1) Hollow silica particles Dispersion with 20% solids by mass, surface treated with a silane coupling agent having a methacryloyl group, average particle size 55 nm (2) Non-hollow silica particles Solid silica particle dispersion with 30% solids by mass, surface treated with a silane coupling agent having a methacryloyl group, average particle size 12.5 nm

[0133] The following binder resins were used. Table 2 shows the solid content ratios. (3) Binder resin PETA: Pentaerythritol (tri / tetra)acrylate, manufactured by Nippon Kayaku Co., Ltd., product name "KAYARAD PET-30" DPHA: Dipentaerythritol (hexa / penta)acrylate, manufactured by Nippon Kayaku Co., Ltd., product name "KAYARAD DPHA"

[0134] The following photopolymerization initiators and leveling agents were used: Table 2 shows the percentage of solid content when the binder resin (solid content) is taken as 100 parts by mass. (4) Photopolymerization initiator Manufactured by IGM Resins, product name "Omnirad127" 10 parts by mass (5) Leveling agent (a) Silicone-based (Si-based-2) leveling agent: 10 parts by mass of "X-22-164E" manufactured by Shin-Etsu Chemical Co., Ltd.

[0135] As the solvent, methyl isobutyl ketone and propylene glycol monomethyl ether were used. The mixing ratio was methyl isobutyl ketone / propylene glycol monomethyl ether = 60 / 40 (mass ratio). The blending amount of the mixed solvent was 5,000 parts by mass per 100 parts by mass of the binder resin (solid content).

[0136] <Coating solution 3 for forming low refractive index layer> The following hollow silica particles and non-hollow silica particles were used. Table 2 shows the blending amounts (solid content) of hollow silica particles and non-hollow silica particles (solid silica particles) in parts by mass when the membrane components (solid content) is 100 parts by mass. (1) Hollow silica particles Dispersion in isopropyl alcohol with a solid content of 20% by mass, refractive index of 1.30, average particle size of 60 nm (2) Non-hollow silica particles Spherical silica sol (solid silica particles), isopropyl alcohol dispersion with 25% solid content, surface treated with a silane coupling agent having a methacryloyl group, average particle size 10.5 nm

[0137] (3) Membrane components The following reactive silanes were used as the raw material for the film component (SiO2). 3-Methacryloxypropyltrimethoxysilane

[0138] The following photopolymerization initiators were used: Table 2 shows the percentage of solid content when the film components (solid content) is taken as 100 parts by mass. (4) Photopolymerization initiator Manufactured by IGM Resins, product name "Omnirad369" 8.9 parts by mass

[0139] The low refractive index layer-forming coating liquid 3 was prepared by the following steps. First, a hollow silica particle dispersion, a non-hollow silica particle dispersion, and isopropyl alcohol were mixed in a ratio of 20 / 8 / 25 (mass ratio) to obtain a silica particle dispersion. A reactive silane (3-methacryloxypropyltrimethoxysilane) was added dropwise to this silica particle dispersion and mixed. The mixing ratio was reactive silane:silica particle dispersion = 100:1432 (mass ratio). A 0.4M aqueous nitric acid solution was added dropwise to the mixed liquid while stirring, and the reactive silane was hydrolyzed. The photopolymerization initiator and solvent (isopropyl alcohol) were added to the mixed liquid after hydrolysis, and mixed to obtain a coating liquid 3 for forming a low refractive index layer (solid concentration 3.5 mass %).

[0140] (Examples 1, 4 to 7, Comparative Examples 1 to 2) The coating solution 1 for forming a hard coat layer having the above-mentioned formulation was applied onto an acrylic film (refractive index 1.50) having a thickness of 80 μm, and then dried at 70° C. for 1 minute to volatilize the solvent. Then, the coating solution was irradiated with ultraviolet light (100 mJ / cm 2 ) to form a hard coat layer (dry thickness: 10 μm). The coating solution 1 for forming a high refractive index layer having the above-mentioned formulation was applied onto the hard coat layer, and then dried at 70°C for 1 minute to volatilize the solvent. 2 ) to form a high refractive index layer (dry thickness: 150 nm). On the high refractive index layer, the coating solution 1 for forming the low refractive index layer having the formulation shown in Tables 1 and 2 was applied, and then dried at 60°C for 1 minute to volatilize the solvent. 2 ) to form a low refractive index layer (dry thickness: 100 nm), thereby obtaining antireflection members of Examples 1 and 4 to 7 and Comparative Examples 1 and 2.

[0141] Example 2 Each layer was formed under the same conditions as in Example 1, except that the drying conditions after coating of the low refractive index layer-forming coating liquid 1 were 50° C.×1 minute, to obtain an antireflection member of Example 2.

[0142] Example 3 Each layer was formed under the same conditions as in Example 1, except that the drying conditions after coating of the low refractive index layer-forming coating liquid 1 were 100° C.×1 minute, to obtain an antireflection member of Example 3.

[0143] Example 8 Except for not forming the high refractive index layer, each layer was formed under the same conditions as in Example 1 to obtain an antireflection member of Example 8.

[0144] Comparative Example 3 The coating solution 1 for forming a hard coat layer having the above-mentioned formulation was applied onto an acrylic film (refractive index 1.50) having a thickness of 80 μm, and then dried at 70° C. for 1 minute to volatilize the solvent. Then, the coating solution was irradiated with ultraviolet light (100 mJ / cm 2 ) to form a hard coat layer (dry thickness: 10 μm). The coating solution 2 for forming a high refractive index layer having the above-mentioned formulation was applied onto the hard coat layer, and then dried at 70°C for 1 minute to volatilize the solvent. 2 ) to form a high refractive index layer (dry thickness: 150 nm). On the high refractive index layer, the coating solution 1 for forming the low refractive index layer having the formulation shown in Table 2 was applied, and then dried at 60°C for 1 minute to volatilize the solvent. 2 ) to form a low refractive index layer (dry thickness: 100 nm), and an antireflection member of Comparative Example 3 was obtained.

[0145] Comparative Example 4 Except for not forming the high refractive index layer, each layer was formed under the same conditions as in Comparative Example 3, to obtain an antireflection member of Comparative Example 4.

[0146] Comparative Example 5 The hard coat layer forming coating solution 2 having the above-mentioned formulation was applied onto an acrylic film (refractive index 1.50) having a thickness of 80 μm, and then dried at 70° C. for 1 minute to volatilize the solvent. Then, the film was irradiated with ultraviolet light (50 mJ / cm 2 ) to form a hard coat layer (dry thickness: 12 μm). The coating solution 2 for forming the low refractive index layer having the above-mentioned formulation was applied onto the hard coat layer, and then dried at 70°C for 1 minute to volatilize the solvent. 2 ) to form a high refractive index layer (dry thickness: 100 nm). The coating solution 2 for forming the low refractive index layer having the above-mentioned formulation was applied onto the high refractive index layer, and then dried at 60°C for 1 minute to volatilize the solvent. 2 ) to form a low refractive index layer (dry thickness: 100 nm), and an antireflection member of Comparative Example 5 was obtained.

[0147] Comparative Example 6 The above-described coating solution 1 for forming a hard coat layer was applied onto an acrylic film (refractive index 1.50) having a thickness of 80 μm, and then dried at 70° C. for 1 minute to volatilize the solvent. Then, the coating solution was irradiated with ultraviolet light (100 mJ / cm 2 ) to form a hard coat layer (dry thickness: 10 μm). The coating solution 3 for forming a high refractive index layer having the above-mentioned formulation was applied onto the hard coat layer, and then dried at 70°C for 2 minutes to volatilize the solvent. 2 ) to form a high refractive index layer (dry thickness: 100 nm). The coating solution 3 for forming the low refractive index layer having the above-mentioned formulation was applied onto the high refractive index layer, and then dried at 60°C for 1 minute to volatilize the solvent. 2 ) to form a low refractive index layer (dry thickness: 105 nm). Next, a 0.1 wt% solution was obtained by diluting "Optool DSX-E (registered trademark)" manufactured by Daikin Industries, Ltd. with "Demnum Solvent SOL-1" manufactured by Daikin Industries, Ltd. This solution was applied onto the low refractive index layer using a bar coater and heated at 120°C for 1 minute to form a coating layer with a thickness of about 2 nm, and an antireflection member of Comparative Example 6 was obtained.

[0148] Comparative Example 7 As Comparative Example 7, a commercially available MacBook Pro (15-inch, 2016 model) manufactured by Apple Inc. was disassembled, and an anti-reflection member was taken out. The surface of the anti-reflection member (the surface facing the user) was appropriately cut / cut to an evaluation / measurement size, and the evaluations and measurements of 1-2 to 1-6 were performed.

[0149] [Table 1]

[0150] [Table 2]

[0151] From the results in Table 1, it can be confirmed that the antireflection members of Examples 1 to 8, in which the ratio of Si element is 10.0 atomic % or more and 18.0 atomic % or less and the ratio of C element (C / Si) when the ratio of Si element is converted to 100 atomic %, is 180 atomic % or more and 500 atomic % or less, have good scratch resistance such as steel wool resistance and oil dust resistance. As shown in Fig. 3, the antireflection member of Example 1 had hollow silica particles and non-hollow silica particles uniformly dispersed in the low refractive index layer.

[0152] In contrast, as shown in Table 2, the antireflection members of Comparative Examples 1 to 7 all had Si element ratios and C / Si that did not satisfy the above ranges, and were poor in abrasion resistance such as steel wool resistance and oil dust resistance. In the antireflection member of Comparative Example 2 shown in Fig. 4, hollow silica particles are exposed on the surface of the low refractive index layer, and therefore it is believed that steel wool and oil dust sand easily enter through the gaps between the hollow silica particles, resulting in poor abrasion resistance. In the antireflection member of Comparative Example 5 shown in Fig. 5, non-hollow silica particles are exposed on the surface of the low refractive index layer, and therefore it is believed that the non-hollow silica particles are easily separated from the film by abrasion, resulting in poor abrasion resistance.

[0153] Although not shown in the table, by changing the binder composition of the low refractive index layer in Examples 1 to 8 (for example, a mixture of ditrimethylolpropane tetraacrylate / trimethylolpropane PO-modified (n ≒ 2) triacrylate = 23 / 77, etc.) and adjusting the type of solvent and drying temperature, antireflection members with the Si element ratio and C / Si within the above ranges also had equivalent scratch resistance.

[0154] (Examples 9 to 12) Using the same antireflection member as in Example 1, a steel wool resistance test and an oil dust resistance test were carried out while changing the test environment as shown in Table 3. The other test conditions were the same as those described in 1-4 and 1-5.

[0155] [Table 3]

[0156] A temperature of 16 to 30°C and a relative humidity of 30 to 70% correspond to a general use environment of an image display device equipped with an antireflection member. The results in Table 3 show that the steel wool resistance and oil dust resistance of the antireflection member of the present invention hardly change even if the use environment is different. [Explanation of symbols]

[0157] 100,200 Anti-reflective material 110 Transparent base material 120 Hard coat layer 130 Low refractive index layer 132 Hollow Silica Particles 134 Non-hollow silica particles 140 High refractive index layer 142 High refractive index particles

Claims

1. An antireflection member comprising a low refractive index layer on a transparent substrate, the low refractive index layer contains a binder resin, hollow silica particles, and non-hollow silica particles, The hollow silica particles have an average particle size of 50 nm or more and 100 nm or less, and the non-hollow silica particles have an average particle size of 5 nm or more and 20 nm or less, a ratio of Si element attributable to the silica particles to all elements, which is obtained by analyzing a region of the low refractive index layer from the surface opposite to the transparent substrate to a depth of 10 nm by X-ray photoelectron spectroscopy, is 10.0 atomic% or more and 18.0 atomic% or less, and a ratio of C element, when the ratio of Si element is converted to 100 atomic%, is 180 atomic% or more and 500 atomic% or less, An anti-reflection member, wherein when the thickness of the low refractive index layer is divided into three equal parts and defined as a first region, a second region, and a third region in that order from the transparent substrate side, at any location within the first region and any location within the second region, the ratio of Si element belonging to the silica particles to all elements is 10.0 atomic % or more and 18.0 atomic % or less, and the ratio of C element when the ratio of the Si element is converted to 100 atomic % is 180 atomic % or more and 500 atomic % or less.

2. 2. The antireflection member according to claim 1, wherein a ratio of F element to all elements obtained by analysis by X-ray photoelectron spectroscopy in a region from a surface of the low refractive index layer opposite to the transparent substrate to a depth of 10 nm is 0.5 atomic % or less.

3. 3. The antireflection member according to claim 1, wherein Rz is 110 nm or less, Ra is 15 nm or less, and Rz / Ra is 22.0 or less, where Rz is the maximum height roughness of the low refractive index layer surface and Ra is the arithmetic mean roughness of the low refractive index layer surface.

4. 4. The anti-reflection member according to claim 1, wherein a ratio of an average particle size of the non-hollow silica particles to an average particle size of the hollow silica particles is 0.29 or less.

5. 5. The anti-reflection member according to claim 1, wherein the surfaces of the hollow silica particles and the non-hollow silica particles are coated with a silane coupling agent.

6. 6. The antireflection member according to claim 1, wherein the low refractive index layer has an indentation hardness of 480 MPa or more as measured by a nanoindentation method.

7. 7. The antireflection member according to claim 1, wherein the low refractive index layer has a restoration rate of 80% or more by a nanoindentation method.

8. The antireflection member according to claim 3 , wherein Rz / Ra is 10.66 or less.

9. A polarizing plate having a transparent protective plate, a polarizer, and a transparent protective plate in this order, at least one of the two transparent protective plates being the anti-reflection member according to any one of claims 1 to 8.

10. 9. An image display device comprising the antireflection member according to claim 1 on a display element.

11. An antireflective article comprising the antireflective member according to claim 1 on a member.

Citation Information

Patent Citations

  • Antireflection laminate

    JP2008107792A

  • Antireflection film and its manufacturing method

    JP2018535440A

  • Epoxy resin composition

    JP1985011527A

  • Antireflection film

    JP2007078711A

  • anti-reflection film

    JP2018533068A